Pengembangan Aplikasi Percakapan Daring Pengelolaan Hubungan Pelanggan (Studi Kasus PT. Indi Platform Raksasa) - Faris Nauval Abdurrahman; Adam Hendra Brata; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In running its business PT. Indi Platform Raksasa use WhatsApp instant messaging application as a means of communication to its current customers or potential customers. There are 50 admins who accept orders and provide information services to customers. On one day each admin can receive 1500 to 2000 messages per day. To make it easier for admins to remember customer categories, a customer recording system was created using excel, but as the number of messages that come in every day grows, the recording process becomes less efficient and requires a lot of time and effort. In addition, the performance of each admin cannot be controlled because there is no tool to measure admins performance. In this research the author tries to apply the use of information systems to overcome some of the problems above. In developing an information system the author uses the waterfall method. From the results of the requirement gathering of customer online chat management application, there are 2 actors, also there are 21 functional requirements and 1 non-functional requirement. From the results of the requirement gathering, a system design is made that produces 9 classes on the backend and 2 classes on the front end, besides that there are 6 entities in the design of the data structure. In the testing of the developed system, the results of unit testing, integration testing, and validation testing are 100% valid, while the reliability test for the system got 1261 Minutes on the MTBF score.